Using Artificial Intelligence (Ai) Chatgpt As A Writing Tool: Based On Efl Students’ Perceptions - Siregar, Hawalaina Rahman Hasan; Siregar , Deasy Yunita; Damanik , Emeliya Sukma Dara (CV. ITTC INDONESIA, 2024)
In this era of technological advancement, the use of AI tools in education is growing. There is a need to understand how AI can support the learning process and help students overcome challenges, particularly in writing. This study investigated EFL students' attitudes toward the use of ChatGPT as an AI writing tool. The study took a qualitative approach with a phenomenological design. Data collection included interviews with five English Education students at UIN North Sumatra who were thought to be the most experienced in order to gather detailed perspectives. The collected data was then analyzed using the thematic analysis technique.The findings revealed that students held positive perceptions. Students emphasized ChatGPTT's usefulness in the writing process and role in overcoming writing challenges. Students found that ChatGPT is effective in providing instant feedback and immediate support for their writing. Chatgpt has benefits in time efficiency, helping in finding topics and developing ideas, increasing vocabulary, and improving grammar. However, there were some challenges such as limited data or knowledge in ChatGPT, which may lead to inaccurate results, as well as creating laziness and potential dependency, and network problem. Based on these findings, it is recommended to use ChatGPT only as a reference or consultation tool only, students should continue to use their critical thinking skills, and ChatGPT answers should be verified with reliable sources. The findings of this study suggest that, while ChatGPT can significantly aid the writing process, educators and students should be aware of its limitations.